Designing a digital portfolio as an instrument to address literary texts in the EFL classroom - Lasa-Álvarez, Begoña (Glottodidactica, 2023)
This study discusses the use of a digital portfolio as a means of incorporating literary texts as didactic resources in the EFL classroom. It is structured as follows: (i) introduction, (ii) advantages of using literary texts in the EFL classrooms; (iii) an analysis of portfolios in general, and digital portfolios in particular; (iv) a description of the current proposal for teaching and learning, involving an e-portfolio which focuses on the book Frankenstein, or The Modern Prometheus, by Mary Shelley; and (v) conclusion. In using such a digital resource, students not only read the book itself, but need to complete the three components of the portfolio – a language diary, a language biography, and a section about literary landscapes – all at the different stages in the learning process. The benefits to students were expected to include a positive effect on their overall acquisition of the foreign language, along with the development of other skills and competences, particularly self-assessment and digital competence, while also gaining knowledge about the literary text in question.